Enzyme inhibitory and antioxidant activities of traditional medicinal plants: Potential application in the management of hyperglycemia - Gulati Vandana; Harding Ian H; Palombo Enzo A (BMC, 2012)
Abstract Background Traditional Indian and Australian medicinal plant extracts were investigated to determine their therapeutic potential to inhibit key enzymes in carbohydrate metabolism, which has relevance to the management of hyperglycemia and type 2 diabetes. The antioxidant activities were also assessed. Methods The evaluation of enzyme inhibitory activity of seven Australian aboriginal medicinal plants and five Indian Ayurvedic plants was carried out against α-amylase and α-glucosidase. Antioxidant activity was determined by measuring (i) the scavenging effect of plant extracts against 2, 2-diphenyl-1-picryl hydrazyl (DPPH) and 2, 2'-azinobis-3-ethylbenzothiazoline-6-sulfonate (ABTS) and (ii) ferric reducing power. Total phenolic and total flavonoid contents were also determined. Results Of the twelve plant extracts evaluated, the highest inhibitory activity against both α-amylase and α-glucosidase enzymes was exerted by Santalum spicatum and Pterocarpus marsupium with IC50 values of 5.43 μg/ml and 0.9 μg/ml, respectively, and 5.16 μg/ml and 1.06 μg/ml, respectively. However, the extracts of Acacia ligulata (IC50 = 1.01 μg/ml), Beyeria leshnaultii (0.39 μg/ml), Mucuna pruriens (0.8 μg/ml) and Boerhaavia diffusa (1.72 μg/ml) exhibited considerable activity against α-glucosidase enzyme only. The free radical scavenging activity was found to be prominent in extracts of Acacia kempeana, Acacia ligulata followed by Euphorbia drummondii against both DPPH and ABTS. The reducing power was more pronounced in Euphorbia drummondii and Pterocarpus marsupium extracts. The phenolic and flavonoid contents ranged from 0.42 to 30.27 μg/mg equivalent of gallic acid and 0.51 to 32.94 μg/mg equivalent of quercetin, respectively, in all plant extracts. Pearson's correlation coefficient between total flavonoids and total phenolics was 0.796. Conclusion The results obtained in this study showed that most of the plant extracts have good potential for the management of hyperglycemia, diabetes and the related condition of oxidative stress.